Proficiency and Giftedness: The Role of Language Comprehension in Gifted Identification and Achievement. (December 2020) - Hamilton, Rashea; Long, Daniel; McCoach, D. Betsy; Hemmler, Vonna; Siegle, Del; Newton, Sarah D.; Gubbins, E. Jean; Callahan, Carolyn M.
English learners (ELs) are the fastest growing population of students in the United States and currently represent nearly 10% of public school enrollment; however, they also constitute less than 3% of gifted program enrollment in these schools. Although an increasing number of studies explore this underrepresentation, research that specifically examines the role of language proficiency in gifted identification is limited. This study explored the role of several factors on ELs' time to reclassification (the point at which students are considered to have reached language proficiency and are no longer classified as ELs) and, in turn, being identified for gifted services. The findings suggested notable demographic and socioeconomic influences on the time to reclassification of ELs. Students who were reclassified earlier tended to be enrolled in schools with more gifted students and had a greater probability of being identified as gifted.